Assessing cellular internalization and endosomal escape abilities of novel BUFII-Graphene oxide nanobioconjugates - Torres-Vanegas, Julian Daniel; Cifuentes, Javier; Puentes, Paola Ruiz; Quezada, Valentina; Garcia-Brand, Andres J.; Cruz, Juan C.; Reyes, Luis H. (Frontiers in Chemistry, 2022)
Cell-penetrating agents based on functionalized nanoplatforms have emerged as a promising approach for developing more efficient and multifunctional delivery vehicles for treating various complex diseases that require reaching different intracellular compartments. Our previous work has shown that achieving full cellular coverage and high endosomal escape rates is possible by interfacing magnetite nanoparticles with potent translocating peptides such as Buforin II (BUF-II). In this work, we extended such an approach to two graphene oxide (GO)-based nanoplatforms functionalized with different surface chemistries to which the peptide molecules were successfully conjugated. The developed nanobioconjugates were characterized via spectroscopic (FTIR, Raman), thermogravimetric, and microscopic (SEM, TEM, and AFM) techniques. Moreover, biocompatibility was assessed via standardized hemocompatibility and cytotoxicity assays in two cell lines. Finally, cell internalization and coverage and endosomal escape abilities were estimated with the aid of confocal microscopy analysis of colocalization of the nanobioconjugates with Lysotracker Green®. Our findings showed coverage values that approached 100% for both cell lines, high biocompatibility, and endosomal escape levels ranging from 30-45% and 12-24% for Vero and THP-1 cell lines. This work provides the first routes toward developing the next-generation, carbon-based, cell-penetrating nanovehicles to deliver therapeutic agents. Further studies will be focused on elucidating the intracellular trafficking pathways of the nanobioconjugates to reach different cellular compartments.